1982
DOI: 10.1016/0021-9797(82)90077-7
|View full text |Cite
|
Sign up to set email alerts
|

Energy dissipation during stationary flow of suspensions of hydrophilic and hydrophobic glass spheres in organic liquids

Abstract: Suspensions of both hydrophilic and hydrophobic glass spheres in dioctylphthalate behave similarly to suspensions of hydrophilic glass spheres in glycerol + water mixtures: Newtonian behavior is shown up to a solid volume fraction (Cv) of 0.4; at larger Cv values, Bingham behavior is observed with a yield value steeply increasing at cv > 0.45. Suspensions of hydrophobic glass spheres in glycerol + water mixtures, on the other hand, already show deviations from Newtonian behavior at Cv < 0.1. The phenomena indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
14
0

Year Published

1983
1983
1994
1994

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 12 publications
(12 reference statements)
4
14
0
Order By: Relevance
“…In dioctylphthalate (DOP) as a medium (apolar), no difference in steady flow rheological behavior could be observed between suspensions of unsilanized glass beads (hydrophilic) on the one hand, and suspensions of silanized glass beads (hydrophobic) on the other (6). The relative viscosities are identical for suspensions ofhydrophilic and hydrophobic glass beads in DOP, and for suspensions of hydrophilic glass beads in glycerol, a polar system.…”
Section: Introductionmentioning
confidence: 67%
See 2 more Smart Citations
“…In dioctylphthalate (DOP) as a medium (apolar), no difference in steady flow rheological behavior could be observed between suspensions of unsilanized glass beads (hydrophilic) on the one hand, and suspensions of silanized glass beads (hydrophobic) on the other (6). The relative viscosities are identical for suspensions ofhydrophilic and hydrophobic glass beads in DOP, and for suspensions of hydrophilic glass beads in glycerol, a polar system.…”
Section: Introductionmentioning
confidence: 67%
“…Two of the present authors, in a previous paper (6), suggested that sheet formation by particles during shear (1 1-13) is held responsible for the shear-thinning character. On calculating the energy dissipation per unit of volume and time in simple shear by means of = T*'~, [21 one arrives at the conclusion that it is composed of two parts, ~1 = /JPL*+ 2 [3] ~2 = z0*+.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rheological measurements were performed in an Epprecht 15T-FC rotation viscometer (Contraves AG, Ztirich) with rotating inner cylinder (~: 1.50 cm) and stationary outer cylinder (inner ~: 1.90 cm); effective length 5.98 cm [8]. Rheological measurements were generally performed in suspensions with c~ = 0.25.…”
Section: Apparatus and Proceduresmentioning
confidence: 99%
“…T h u s , f = 7 can be obtained, at q = 2, by f ' = 4, which can be obtained from (8) throug h 6 / a = 0.1 and ro/a = 2.02. These values appear to be reasonable.…”
Section: Resullsmentioning
confidence: 99%